An Unveiling the Enigma: Case Series of Retroperitoneal Tumors and literature review - Pallabi Purkayastha; Rama Das; Rhituparna Das (Tropical Journal of Pathology and Microbiology, 2025)
Introduction: Retroperitoneal tumours (RPTs) are a diverse group of lesions that arise in the retroperitoneum and pelvic space. The histological spectrum of retroperitoneal masses is broad, ranging from major aggressive malignancies to benign lesions.Objective: This case series and literature review aimed to study the incidence of retroperitoneal tumours presenting in a diverse array encountered in clinical practice, diagnosed on cytology or biopsy.